How Free Trade Agreements Affect Exports and Imports in Vietnam - Oanh, Nguyen Thi Hoang (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2017)
The important year of 1995 marked Vietnam’s first integration as a member of ASEAN. By 2016, Vietnam had negotiated, signed, and implemented sixteen free trade agreements. They include both multilateral and bilateral free trade agreements such as the China-ASEAN, Vietnam-Chile, and Vietnam-Japan agreements. By signing free trade agreements Vietnam can increase trade flows in bilateral and multilateral developed-country FTA scenarios. Trade creation and diversion can be found in multilateral developing-country FTA scenarios and the author finds the impacts of each free trade agreement is different if analyzed for each 2-digit commodity. Keywords Free trade agreement, trade, import, export.t commodity References [1] Baier, S.L., Bergstrand, J.H., “Do free trade agreements actually increase members’ international trade?”, Journal of International Economics, 71 (2007), 72-95. [2] Chong, Soo Yuen & Hur, Jung, “Small Hubs, Large Spokes and Overlapping Free Trade Agreements”, The World Economy, 10.1111/j (2008), 1467-9701. [3] Hur, J., Alba, J. D., & Park, D., “Effects of hub-and-spoke free trade agreements on trade: A panel data analysis”, World Development, 38 (2010) 8, 1105-111. [4] McDonald, S. & Walmsley, Terrie, “Bilateral Free Trade Agreements and Customs Unions: The Impact of the EU Republic of South Africa Free Trade Agreement on Botswana”, The World Economy, 10.1111/j (2008),1467-9701. [5] Pan, S., Welch, M., Mohanty, S., Fadiga, M., & Ethridge, D., “Welfare analysis of the Dominican Republic-Central America-United States free trade agreement: The cotton textile and apparel industries”, The International Trade Journal, Vol. XXII (2008) 2, 1521-0545. [6] Benedictis, L., Santis, R., Vicarelli, C., “Hub-and-Spoke or else? Free trade agreements in the “enlarged” European Union”, The European Journal of Comparative Economics, 2 (2005) 2, 245-260. [7] Nguyen, Q.H., & Nguyen, T.H., “The impact of free trade agreement on trade flow of goods in Vietnam”, Vietnam Economist Annual Meeting, 2015 [8] Das, R.U., Rishi, M., Dubey, J.D., “Asean plus six and successful FTAS: Can India propel intra-industry trade flows?”, The Journal of Developing Areas, 50 (2016) 2. [9] Hayakawa, K., “Impact of diagonal accumulation rule on FTA utilization: Evidence from bilateral and multilateral FTAs between Japan and Thailand”, J. Japanese Int. Economies, 32 (2014), 1-16. [10] Jennifer Y. Leung, “Bilateral vertical specialization between the U.S. and its trade partners - before and after the free trade agreements”, International Review of Economics and Finance, 45 (2016), 177-196. [11] Jongwanich, J., & Kohpaiboon, A., “Exporter responses to FTA tariff preferences: evidence from Thailand”, Asian Pacific Economic Literature (2017). [12] Lakatos, C., & Walmsley, T., “Investment creation and diversion effects of the ASEAN-China free trade agreement”, Economic Modelling, 29 (2012), 766-779. [13] Vanhnalat, B. at el., “Assessment the Effect of Free Trade Agreements on Exports of Lao PDR”, International Journal of Economics and Financial Issues, 5 (2015) 2, 365-376. [14] Vietnam Chamber of Commerce and Industry (VCCI), “Freedom of international trade in Vietnam”, Research report, Vietnam, 2015.